TRACES OF AESTHETIC LANGUAGE IN THE LYRICS OF RIO SATRIO'S ALBUM CERITA DAUN DAN BUMI - Arina Lutfiatuzzahro; Rosita Sofyaningrum (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study examines the use of stylistic elements in the lyrics of Akun Daun dan Bumi, an album by Rio Satrio, which reflects poetic expressions of human emotions through natural imagery. The purpose of this research is to describe the forms and functions of figurative language, diction, and imagery in constructing meaning and aesthetic value in the song lyrics. This research employs a qualitative descriptive method with a stylistic approach. The data source consists of eight song lyrics from the album Daun dan Bumi Stories. Data were collected through documentation and close reading techniques, while data analysis was conducted by identifying, classifying, and interpreting figurative language, diction, and imagery based on stylistic theory. The results show that the lyrics dominantly employ personification, metaphor, and simile as forms of figurative language, which function to animate natural elements as representations of human feelings. The diction used is predominantly connotative, simple, and poetic, strengthening the emotional atmosphere of the lyrics. Meanwhile, visual, auditory, and emotional imagery play an essential role in enhancing the imaginative experience of listeners. Overall, the integration of figurative language, diction, and imagery contributes significantly to the depth of meaning and aesthetic quality of the album's lyrics.